Comparative study of context-based science curriculum in Indonesia and Malaysia - Ira Nofita Sari; Lia Angraeni; Kamalawati binti Dolhan; Chua Sim Huat (Universitas PGRI Pontianak, 2024)
This study examines the characteristics and approaches of context-based science curricula in Indonesia and Malaysia through a qualitative descriptive-comparative design. The study aims to identify curriculum orientations, forms of contextual integration, and differences in structural implementation between the two education systems. Data were collected through document analysis of official national science curriculum frameworks and supported by relevant scholarly literature. The findings indicate that both countries adopt a context-based orientation in science education, emphasizing the connection between scientific concepts and real-life situations. However, differences are found in the depth and structure of contextual integration. The Indonesian curriculum demonstrates greater flexibility, positioning context primarily as a conceptual linkage adaptable to local conditions. In contrast, the Malaysian curriculum integrates context more systematically within instructional design to strengthen conceptual understanding and application. These findings highlight the importance of balancing contextual relevance and structural coherence in curriculum development. The study contributes to comparative curriculum discourse and provides insights for strengthening context-based science education in diverse educational settings.